Between Metaphor and Identity: the Taste of Wine in Italian Cinema (Itinera, 2017)
This paper aims to investigate the ways in which the wine was represented in the Italian cinema, through some exemplary movies chosen from particularly representative genres: such as neorealism, the Italian comedy and authorâs cinema. Our analysis will show that the wine tasting, in the Italian cinema, has managed very well symbolize, from time to time: conviviality, individual memory, differences of class, sex, death, and finally, the sacred and the religious.Â